The Importance of Applying the Membership Value Toward Savings and Loans Cooperatives in Indonesia - Ayup Suran Ningsih; Duhita Driyah Suprapti; Nurul Fibrianti (Faculty of Law, Sriwijaya University, Indonesia, 2019)
Cooperative Loans and Savings (KSP) is a business entity that having an essential role as an alternative capital fund which is faster and based on the Membership Principle. According to Law No 25 the Year 1992 concerning Cooperatives states that Cooperatives in Indonesia should operate under the Membership Principle. Cooperatives have social characteristics in the form of prioritizing mutual benefits and interests rather than personal interests and benefits. Thus, cooperatives must become the spearhead of the national economy by collecting and distributing funds. However, the reality, there are still numerous frauds in the process of collecting and distributing funds to raise the deposit and also the high interest and the high late charge. The problem appeared is how the actual management of cooperatives loans and savings to carry out their duties and functions. This research is also dealt with the extent of supervision, which is mandated by the law. KSP needs a proper procedural of supervision for their organization. The Financial Services Authority (OJK) is expected to work together with the Ministry of Cooperative and SMEs Office to supervise Cooperative Loans and Savings because it is found that many injustices have been fallen debtors and it is urgent to revise the law and make KSP is under OJK's supervision. The objective of this research is to examine the management of Cooperative Loans and Savings in Indonesia. The other aim of this research is to provide recommendation and consideration for the Indonesian government to strengthen the supervision of Cooperative Loans and Savings under OJK because there is malpractice regarding the term of interest in KSP. The research method used in this article is the statute method, which is supported by an empirical juridical approach in KSP Mitra Usaha Perkasa